MICROSOFT ACCESS APPLICATION SUPPORT AS MAKING TAPE AND COMPACT DISK CATALOGING IN PT. SUARA TUNGGAL ANGKASA RAYA - Widya Precillia Sakul; Sunarto Usna, Drs, Skom, MMSI (Jurnal Sistem Informasi, 2003)
In this paper the authors take the title "Application of Administrative ServicesSupport Program Library STMIK Jakarta STI & K By using Microsoft Visual Basic6.0." Library is the place to get information by reading and conducting research or tosay where the source of knowledge, but in its development, management feels lessutilization of the library who need them.In general, the library in Indonesia is still using a technology that can not be reliedupon, or it can be said is still very manual, so very difficult for the administration ofthe library database. Whereas we know that the library is one of the informationwindow that can open and develop insights into thinking that a national society cancontribute to the intellectual life of the nation.Where in this case is a discourse for the writer to develop a library function that isdistributed faster and reliable in terms of delivery and administration easier in termsof library databases.For that it would the good if the application has been running or not, always lookingfor the right solution so that the function library we can really feel.